Urgensi Saksi dalam Permohonan Cerai Talak menurut Fiqih Munakahat (Studi Putusan Nomor: 450/PDT.G/2025/PA.LK Pengadilan Agama Tanjung Pati) - Natasya Pratama Putri; Endri Yenti (Lembaga Yasin AlSys, 2026)
Although studies on evidence in divorce cases have been widely conducted, research that specifically integrates judicial considerations with the perspective of fiqh munakahat regarding the urgency of witnesses in petitions for divorce by talak remains limited. This study aims to analyze judicial considerations regarding witness evidence in Decision Number 450/Pdt.G/2025/PA.LK of the Tanjung Pati Religious Court and to examine the urgency of witnesses from the perspective of fiqh munakahat. This study used a qualitative approach with a case study design. The research informants were selected through purposive sampling, including judges of the Tanjung Pati Religious Court who handled the related case. Data were collected through interviews, documentation, and observation, then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The results show that the petition for divorce by talak was rejected because the testimony submitted did not meet the required evidentiary strength, particularly because the witnesses did not have direct knowledge of the disputed events. This finding affirms that witnesses hold an important position in the evidentiary system of divorce by talak cases, both from the perspective of civil procedural law and fiqh munakahat. The conclusion of this study shows that the quality of testimony is a crucial aspect in realizing legal certainty and justice in the resolution of divorce cases. The implications of this study include theoretical contributions to the development of Islamic family law studies and practical implications for judges, academics, and the public in understanding the urgency of valid, relevant, and accountable witness evidence.